Mean versus variability of lipid measurements over 6 years and incident cardiovascular events: More than a decade follow-up - Masrouri, Soroush; Cheraghi, Leila; Deravi, Niloofar; Cheraghloo, Neda; Tohidi, Maryam; Azizi, Fereidoun; Hadaegh, Farzad (Frontiers in Cardiovascular Medicine, 2022)
Background Lipid variability (LV) has emerged as a contributor to the incidence of cardiovascular diseases (CVD), even after considering the effect of mean lipid levels. However, these associations have not been examined among people in the Middle East and North Africa (MENA) region. We aimed to investigate the association of six-year mean lipid levels versus lipid variability with the risk of CVD among an Iranian population. Methods A total of 3700 Iranian adults aged ≥30 years, with 3 lipid profile measurements, were followed up for incident CVD until March 2018. Lipid variability was measured as standard deviation (SD), coefficient of variation (CV), average real variability (ARV), and variability independent of mean (VIM). The effects of mean lipid levels and LV on CVD risk were assessed using multivariate Cox proportional hazard models. Results During a median 14.5-year follow-up, 349 cases of CVD were recorded. Each 1-SD increase in the mean levels of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), TC/high-density lipoprotein cholesterol (HDL-C), and non-HDL-C increased the risk of CVD by about 26-29%; for HDL-C, the risk was significantly lower by 12% (all p values <0.05); these associations resisted after adjustment for their different LV indices. Considering LV, each 1-SD increment in SD and ARV variability indices for TC and TC/HDL-C increased the risk of CVD by about 10%; however, these associations reached null after further adjustment for their mean values. The effect of TC/HDL-C variability and mean lipid levels, except for LDL-C, on CVD risk was generally more pronounced in the non-elderly population. Conclusions Six-year mean lipid levels were associated with an increased future risk of incident CVD, whereas LV were not. Our findings highlight the importance of achieving normal lipid levels over time, but not necessarily consistent, for averting adverse clinical outcomes.